A systematic review of augmented reality in science, technology, engineering and mathematics education - Hidayat, Riyan; Wardat, Yousef (Springer, 2023)
Augmented Reality has found extensive use as an interactive technology in various learning and educational environments. However, a previous systematic review (SR) lacked a framework to identify the various types of augmented reality utilized, the types of technology employed, and the types of augmented parameters involved. The primary objective of this study was to review current studies in which Augmented Reality learning was used to assist Science, Technology, Engineering and Mathematics education. This study was guided by the processes of identification, screening, eligibility, included and data analysis on three search engines which were ERIC, ScienceDirect and Scopus. In reporting this research, the Preferred Reporting Items for Systematic Reviews and Meta-Analysis protocol was followed which identified 42 related articles. Our findings revealed that three popular types of Augmented Reality design were being utilized in Science, Technology, Engineering and Mathematics learning including marker-less Augmented Reality, marker-based Augmented Reality and projection-based Augmented Reality. The SR outputs also indicated that most scholars employed cameras and object markers as technological modalities to support Science, Technology, Engineering and Mathematics education. Finally, 3D and animated elements were widely used augmented components in Science, Technology, Engineering and Mathematics education. One of the significant implications was that comprehending these distinctions could help in the choice of the appropriate Augmented Reality variant for a specific use circumstance and enable the creation of successful Augmented Reality experiences that fulfil predetermined goals.